A DESCRIPTIVE STUDY EXPLORING THE PRINCIPLES OF ASEPSIS TECHNIQUES AMONG PERIOPERATIVE PERSONNEL DURING SURGERY - Adams, Jeanette; Korniewicz, Denise; El-Masri, Maher (Operating Room Nurses Association of Canada Journal, 2011)
Background: Perioperative nurses are expected to demonstrate strict adherence with asepsis principles to prevent surgical site infections (SSIs) as breaching of these principles poses a serious risk of infection to surgical patients. Methods: A descriptive survey was conducted with a convenience sample of 87 perioperative personnel to describe self-reported compliance with the principles of asepsis during surgery. Purpose: The purpose of this study was to examine the practices of perioperative scrub personnel with surgical asepsis. Results: A sizable percentage of participants indicated that they never or rarely observe breaches in the sterile field during surgery with regards to open suction drain systems (46.6%; n = 41), closed suction drain systems (46.6%; n = 41), suture material (39.7%; n = 35), use of surgical instruments (37.5%; n = 33), and prosthetic implants (56.8%; n = 50). Perioperative scrub RNs were less likely to wear shoe covers during surgical procedures than ORTs (M = 3.42 and 4.17; mdn = 3.00 and 5.00 respectively; p = .026). Conclusions: The findings showed areas of compliance and noncompliance with the principles of asepsis. Given that the role of the perioperative nurse is paramount in maintaining surgical integrity, and enhancing positive patient outcomes, strict adherence to surgical asepsis is vital to prevent SSIs and other complications.